Covid 19 in the face of Contemporary International Law - Norouzi, Nima; Ataei, Elham (Brawijaya Law Journal : Journal of Legal Studies, 2021)
The outbreak of Covid-19 is an international crisis that has been unprecedented for the past hundred years. The virus was first reported in Wuhan, China, in late 2019 and gradually spread worldwide. In such circumstances, the effectiveness of international law in protecting human lives and promoting the right to health has been severely tested. More importantly, in the words of Michel Bachelet (A UN official), the Covid-19 has become a benchmark for the international community. This article will analyze how international law deals with the Covid-19 crisis in several areas: First, the World Health Organization’s role as the main body responsible for protecting human healthcare in the face of the Covid-19 outbreak will be analyzed. Second, the international responsibility of States in guaranteeing the right to health will be assessed to determine the effectiveness of international law. Third, the suspension of human rights abuses due to the Covid-19 outbreak emergency will be tested in the international human rights system. Finally, the performance of the UN Security Council in dealing with this pandemic is examined. In each area, the question is to what extent the current structure of international law effectively deals with international crises and preserves human dignity.